2018
DOI: 10.1093/pm/pny133
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectionality of Pain Interference and PTSD Symptoms in Military Veterans: Does Injury Status Moderate Effects?

Abstract: These results indicate that physical symptom management should be a crucial target of psychological intervention for returning veterans with PTSD symptoms and deployment-related injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…After, there was a unidirectional relationship where increases in physical symptoms predicted further increases in subsequent PTSD symptoms, but not vice versa. These findings are consistent with most previous research that showed a bidirectional relationship at first and a unidirectional relationship over time (Carty et al, 2011;Jenewein et al, 2009;Lee et al, 2018;Ravn et al, 2018;Stratton et al, 2014). The extant research is evenly split between whether the unidirectional relationship is between increases in PTSD predicting later increases in physical symptoms or increases in physical symptoms predicting later increases in PTSD symptoms.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…After, there was a unidirectional relationship where increases in physical symptoms predicted further increases in subsequent PTSD symptoms, but not vice versa. These findings are consistent with most previous research that showed a bidirectional relationship at first and a unidirectional relationship over time (Carty et al, 2011;Jenewein et al, 2009;Lee et al, 2018;Ravn et al, 2018;Stratton et al, 2014). The extant research is evenly split between whether the unidirectional relationship is between increases in PTSD predicting later increases in physical symptoms or increases in physical symptoms predicting later increases in PTSD symptoms.…”
Section: Discussionsupporting
confidence: 90%
“…The extant research finds consistent support that baseline levels of PTSD symptoms predict subsequent increases in physical symptoms and baseline levels of physical symptoms predict subsequent increases in PTSD symptoms with study baseline assessments ranging from 24 hours to 3 years after the traumatic event (Carty, O'Donnell, Evans, Kazantzis, & Creamer, 2011;Feinberg et al, 2017;Jenewein, Wittmann, Moergeli, Creutzig, & Schnyder, 2009;Lee et al, 2018;Liedl & Knaevelsrud, 2008;Ravn, Sterling, Lahav, & Andersen, 2018;Stratton et al, 2014). These same studies find inconsistent support that increases in PTSD (from baseline to a second time point) predict further increases in physical symptoms (from a second to a third time point) and vice versa.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…A substantial amount of research has demonstrated a significant association between PTSR and higher levels of various adverse physical health outcomes after trauma including traumatic injury (Afari et al, 2014;Pacella et al, 2013;Zatzick et al, 2003). Such outcomes may include both defined medical illnesses and subjectively reported somatic health complaints related to multiple bodily organs (Green & Kimerling, 2004;Koenen et al, 2017;Lee et al, 2018). PTSD was early on hypothesized to mediate the relationship between trauma exposure and physical health (Schnurr & Jankowski, 1999), and biological, psychological, and behavioral mechanisms have been proposed to be involved (Koenen et al, 2017;Schnurr & Green, 2004).…”
Section: The Role Of Posttraumatic Stress Reactionsmentioning
confidence: 99%
“…Chronic pain and PTSD occur together in veterans more frequently than either condition alone, 3,4 and this comorbidity can have worse implications for well-being than either condition individually. 5,6 Veterans with both conditions report greater psychological distress and functional interference compared with those with chronic pain but without PTSD, and those with chronic pain often report more severe PTSD. 7 The aim of this article is to summarise what is known about why chronic pain and PTSD frequently co-occur, what is known about treatment options, current service provision for UK veterans with both conditions and to provide research recommendations.…”
Section: Introductionmentioning
confidence: 98%